A prospective study to examine the bleeding tendency of patients receiving regular low-dose aspirin therapy (Mustansiria Dental Journal, 2018)
The fear of uncontrolled bleeding often prompts medical practitioners to stopaspirin intake for seven to 10 days before any surgical procedure. This study wasinitiated to evaluate the effect of aspirin on bleeding in patients undergoing oralsurgery.The study group consisted of 39 patients who were subjected to undergo dentalextraction. All patients were receiving 100 milligrams of aspirin daily on a regularbasis. Patients were randomly divided into two groups: those who stopped the aspirintherapy before the procedure and those who continued the aspirin therapy. One hourbefore the procedures, all patients underwent a bleeding time test. In addition, theamount of bleeding during the procedure was measured.The mean (± standard deviation) bleeding time was 1.8 ± 0.47 minutes for patientswho stopped aspirin therapy one week before the procedure. For patients whocontinued aspirin therapy, the bleeding time was 3.1 ± 0.65 minutes. The differencewas statistically significant (P = .004). However, both groups were within the normalbleeding time range, and in both groups, a local hemostatic method was sufficient tocontrol bleeding. No episodes of uncontrolled intraoperative or postoperative bleedingwere noted.Stopping of low-dose aspirin therapy is not a must before oral surgery. Localhemostasis is sufficient to control bleeding.